Effects of Xenon and Hypothermia on Cerebrovascular Pressure Reactivity in Newborn Global Hypoxic—ischemic Pig Model. Issue 11 (November 2013) - Chakkarapani, Elavazhagan; Dingley, John; Aquilina, Kristian; Osredkar, Damjan; Liu, Xun; Thoresen, Marianne
Autoregulation of cerebral perfusion is impaired in hypoxic-ischemic encephalopathy. We investigated whether cerebrovascular pressure reactivity (PRx), an element of cerebral autoregulation that is calculated as a moving correlation coefficient between averages of intracranial and mean arterial blood pressure (MABP) with values between −1 and +1, is impaired during and after a hypoxic-ischemic insult (HI) in newborn pigs. Associations between end-tidal CO2, seizures, neuropathology, and PRx were investigated. The effect of hypothermia (HT) and Xenon (Xe) on PRx was studied. Pigs were randomized to Sham, and after HI to normothermia (NT), HT, Xe or xenon hypothermia (XeHT). We defined PRx >0.2 as peak and negative PRx as preserved. Neuropathology scores after 72 hours of survival was grouped as 'severe' or 'mild.' Secondary PRx peak during recovery, predictive of severe neuropathology and associated with insult severity ( P = 0.05), was delayed in HT (11.5 hours) than in NT (6.5 hours) groups. Seizures were associated with impaired PRx in NT pigs ( P = 0.0002), but not in the HT/XeHT pigs. PRx was preserved during normocapnia and impaired during hypocapnia. Xenon abolished the secondary PRx peak, increased (mean (95% confidence interval (CI)) MABP (6.5 (3.8, 9.4) mm Hg) and cerebral perfusion pressure (5.9 (2.9, 8.9) mm Hg) and preserved the PRx (regression coefficient, −0.098 (95% CI (−0.18, −0.01)), independent of the insult severity.